THE EFFECT OF EMOTIONAL LABOR BEHAVIOR ON EMPLOYEES' BURNOUT LEVEL IN AVIATION INDUSTRY EMPLOYEES. AN AIRLINE COMPANY EXAMPLE (Third Sector Social Economic Review, 2025)
This study aims to deeply examine the effects of emotional labor behaviors of employees in the aviation industry on their burnout levels. In particular, the effects of surface acting, deep acting, and natural emotions on burnout were analyzed. The study covers 300 employees working in an airline company operating in Turkey. Data obtained from the participants were collected through various tools such as demographic information form, emotional labor scale and burnout scale. The collected data were evaluated with descriptive statistics, correlation analysis and regression analysis using the SPSS program. The findings revealed that surface acting showed a positive correlation with burnout, meaning that this type of acting increased burnout levels. On the other hand, it has been observed that deep acting has a negative correlation with reducing burnout, that is, deep acting reduces burnout levels.Additionally, a positive relationship was found between the expression of natural emotions and burnout. Regression analyzes showed that the effects of these variables on burnout were not statistically significant. However, it was concluded that surface acting may slightly increase burnout and deep acting may have a reducing effect on burnout. These findings suggest that the relationship between emotional labor and burnout requires further research.
Keywords: Aviation Enterprises; the effect of emotional labor behaviors on burnout levels.